FACTORS ASSOCIATED WITH TIMELINESS OF RETURN OF MEDICAL RECORD DOCUMENTS FOR HOSPITALIZATION IN RSU TANGERANG SELATAN IN 2023 - Nur Asyah Jamilah; Andriyani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
In Indonesia, a significant portion of medical record files are still returned inaccurately. according to a study conducted at Medan's Estomihi Hospital, which found that 72.41% of returned medical record files were inaccurate. The purpose of this study is to ascertain how the promptness of returning medical record files relates to age, gender, education level, marital status, work shifts, duration of service, and work motivation. This kind of research uses a cross-sectional study design and is quantitative. 59 inpatient nurses made up the study's sample, and they underwent univariate and bivariate testing. The nurse's age (p-value = 0.014), sex (p-value = 0.220), education level (p-value = 0.011), marital status (p-value = 0.930), shift work (p-value = 0.020), tenure (p-value = 0.036), and work motivation (p-value = 0.029) are all related to the timeliness of returning medical record files. Age, education level, work shifts, years of service, and passion for one's job are all factors that affect how quickly medical record files are returned. However, there is no correlation between marital status and gender and how quickly medical record data are returned.